A solar cycle of upper thermosphere density observations from the EISCAT Svalbard Radar. Issue 8 (19th August 2014) - Vickers, H.; Kosch, M. J.; Sutton, E.; Bjoland, L.; Ogawa, Y.; La Hoz, C.
Abstract We exploit a recently developed technique, based on ion‐neutral coupling, which allows estimations of the upper thermospheric neutral density using measurements of ionospheric plasma parameters made by the European Incoherent Scatter (EISCAT) Svalbard Radar (ESR). The technique is applied to a 13 year long data set of measurements for the purpose of studying and quantifying the effect of solar activity on the upper thermospheric density inside the polar cap. We concentrate on the effect of solar activity at 350 km altitude and find a strong linear correlation between the ESR estimates for the atomic oxygen density and the solar irradiance proxy F10.7 index. We use the relationship to isolate variations in the thermospheric density that are present after solar activity influences are removed. Our results show a decrease in the density of a few percent over the 13 year period, which is nevertheless smaller than the uncertainty associated with the decline. We anticipate that the statistical significance of this result will only increase by studying a longer data set. Conjunctions with the CHAMP satellite that show very good agreement is achieved at 350 km especially during low solar activity.